Well-being and job satisfaction of employees aged 50+, perceived organizational support for development and innovation - Rakowska, Anna; Juana-Espinosa, Susana de; Mendryk, Iwona (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
Companies all around Europe are experiencing an increase in the average age of their staff who remain professionally active even after reaching the retirement age. As a result, organizations are increasingly expected to support workers into their senior years. In turn, HR specialists and managers ought to understand the motivations and needs of employees aged 50 and above, especially in terms of encouraging innovative attitudes and facilitating the sense of well-being and satisfaction. This study aimed to determine whether organizational support in the areas of employee development and innovation, as perceived by employees aged above 50, may have an impact upon their levels of work satisfaction and overall well-being. The Partial Least Squares (PLS) approach was applied to reveal the relationships between two specific facets of perceived organizational support, job satisfaction, and well-being. The presented results herein are expected to contribute to HR managers’ improved understanding of the value and importance of senior employees, and to encourage them to adopt more effective HR measures and practices aimed at keeping such workers satisfied and healthy at work, as well as rendering them more involved in their jobs and open to innovation
Argumenta Oeconomica, 2020, Nr 1 (44), s. 143-172